Sistem Pengelolaan Zakat Yayasan Yatim Mandiri Cirebon - Nindiani, Resa; Iman , Chaerul; Zulfikar Hafizd, Jefik (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2023)
Every Muslim recognizes that zakat is one of the pillars of the establishment of Islam that must be fulfilled, the point of zakat is the third pillar of Islam. The management of zakat is carried out by the zakat amil body formed by the government which is organized in the form of an agency or institution. The collection of zakat is carried out by the amil zakat body by receiving or taking from muzakki on the basis of notification from muzakki. The 1999 Zakat Management Law was deemed unable to accommodate the dynamics of society and the state in managing Zakat, hence the 2011 Zakat Management Law was born. This law created controversy among zakat managers, because this law was seen as turning off the role of the community in managing zakat, and trying to centralize the management of zakat. Zakat in the hands of the National Zakat Amil Agency (BAZNAS). This paper aims to examine the management of zakat carried out by the Cirebon Yatim Mandiri Foundation, and how it is collected and distributed by the Cirebon Yatim Mandiri Foundation. The research method used in this paper is field research with a qualitative descriptive approach. The primary data of the study were collected through field observations and interviews with the Cirebon Yatim Mandiri .